Some Aspects of Harmonization of the EU Customs Law and the Customs Law of the Customs Union of Russia, Belarus and Kazakhstan - Galushko, Dmitriy (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
This paper aims at analyzing of the possible ways of harmonization of the EU legal norms and norms of the newly created Customs Union of Russia, Belarus and Kazakhstan as one of the outcomes of the process of Eurasian integration. First, the author examined the process of adoption of the legal basis for functioning of the Customs Union, then, these legal norms were analyzed in the light of the EU law, and finally, the author sets some ways for harmonization between two legal orders, particularly through the procedure of transit.